Gender dalam lokalitas budaya Panginyongan (Analisis strategi aktifis perempuan di Banyumas dalam mengelola konflik rumah tangga) - Fatni Erlina (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
This article aims to find out how the locality value of panginyongan is implemented in Banyumasan culture, through a strategy for managing household role conflicts. The women activists who are active in public spaces, consciously have a dual role, but which factors are the most significant in supporting their harmony are not necessarily understood, so there has been no effort to maintain their existence. This article is a field study that takes a sample of women activists in Banyumas. The process of extracting data is carried out by means of in-depth interviews to determine the gender perception index, then using focus group discussions (FGD) to find out how the informants internalize the Panginyongan cultural values in their lives, especially related to the division of household roles. With the point of view of the subjects studied, the research is expected to produce a thick description of the strategy for managing household role conflicts through the cultural values of panginyongan. The results showed that the equality of positions had permeated through the equivalence of language, speech, attitude and behavior, so that none of the household players felt humiliated or exalted in filling domestic or public duties. If the wife is left for outdoor activities, the husband plays a role in completing the abandoned domestic work, and vice versa.